PERLINDUNGAN NASABAH DEBITUR TERHADAP PERJANJIAN BAKU YANG MENGANDUNG KLAUSULA EKSONERASI PADA BANK UMUM DI BANDARLAMPUNG - Ahmad Jahri (Fiat Justisia: Jurnal Ilmu Hukum, 2016)
Legal protection for debtor as a consumer in banking becomes important which the position of the some parts of credit contract is not balanced. Bank prefer to have a strong bargaining position, so the bank based on the reason of efficiency makes standard contract contain exoneration clause that incriminating debitors. The Government’s Determination Law No. 8 of 1999 on Consumer Protection has been set up the opposition to banning the use of the standard contract. Similarly, the Financial Services Authority (FSA)/ Otoritas Jasa Keuangan (OJK) carried out a function of supervising the financial institution has issued POJK No. 1/POJK.07/2013 on Consumer Protection of Financial Services Sector. The regulations issued to protect consumers especially financial services sector. The result showed that credit contract of the commercial bank in Bandar Lampung still contains exoneration clause that prohibited on The Government’s Determination Law No. 8 of 1999 on Consumer Protection and OJK Regulation No.1/POJK.07/2013 on Consumer Protection of Financial Services Sector. There is a clause that requires the debtors to submit all bank’s guidance and regulations, either already exist or will be set later. The legal consequence of the implementation of exoneration clause in credit contract is the contract can be canceled by law as mentioned in Article 18 paragraph (3) The Government’s Determination Law No. 8 of 1999 on Consumer Protection. The legal protection of debtor as a consumer of banking service has been arranged by the regulations, but the implementation has not effective because still there are abuses by the bank. Therefore, the active role of Financial Services Authority to conduct monitoring and providing strict sanctions to banks that violate the rule. Furthermore, need education for community and have to make a format of standard contract that compatible with rules which formulated by the Financial Services Authority (FSA)/ Otoritas Jasa Keuangan (OJK). Keywords: Exoneration, Clause, Customer Protection, Standard Contract